An Analysis of Students Writing Ability by Composing Narrative Text - Ira Puspita (ETERNAL (English Teaching Journal), 2018)
The study aimed to find out whether any influences compossing narrative text to the students writing ability at seventh grade students of STIT Muhammadiyah Tanjung Redeb and to find out the level ability after students compossing narrative text. The  scope of study writing narrative text at the Seventh Grade Students of STIT Muhammadiyah  Tanjung Redeb. The method of this research is quantitative. The population in this study was the whole seventh grade students in STIT Muhammadiyah  Tanjung Redeb, which is enlisted in the academic year of 2014/2015. The seventh grades belong of one class each classes consisted of about 36 students. The writer takes  15 students of them as the research sample (groub B) by using random sampling (namely a method of sample taking by mixly without paying attention to the grade of number of population. The method of data collection used documentation and test and the method of data analys used SPPS 21 Version. The result showed that shows the pre-test score of the class was 11.617 with standard deviation of 3.065 and the post-test score was 17.617 with standard deviation of 2.146. The post-test scores were higher than the pre-test scores.